Revitalizing Conversations: Lessons From and About the Production of Intersubjective and Intercultural Knowledge - Briones, Claudia Noemi (2021)
Based on our present working-experience with a Mapuche kimche (sage) and a logko (spiritual and political leader), we aim at intervening in broader debates on the intersubjective and intercultural production of knowledge. To do so, we pay special attention to contemporary mandates and pervasive conceptions about forms of practicing a better, more proper anthropology. We approach the problem from three different viewpoints: (a) discomforts and disagreements with naturalized forms of initiating, certifying, informing, writing, citing, and authorizing knowledge; (b) the Mapuche etiquette to converse properly and its various bets on horizontality; (c) review of our own philosophy of language, particularly the concepts of translation and performativity.